KOMPARASI RUANG FISIK GEREJA ST. MARY SINGAPORE DAN RUANG MAYA GEREJA INJILI INDONESIA SETRASARI - Lois Denissa (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2020)
The church as a worship building is designed in such a way as to be able to fulfill its duties as a building, technical requirements, and forms. Shapes as objects that are seen physically are designed and used to make sense of many things. The next form appears as a text or sign that relates the shape to the meaning. Space as well as form as a whole is a representation of the message conveyed to the public. The Church of St. Mary of the Angel was designed with meaningful signs of religiosity, both as icons, indexes, and symbols starting from the design of the site space to the interior details. On the other hand, the visual signs on the Indonesian Evangelical Church of Setrasari are not shown much, even from its location on the 2nd floor Giant Supermarket on the 1st floor very opposite. This research is important to do to see the relation of object markings in real physical worship buildings and the meaning they represent with other worship buildings with meanings born of non-physical or factual signs. The method in this study uses a comparative qualitative method at the study stage and ethnographic semiotics method at the analysis stage, namely through behavior patterns and in-depth interviews. Physical markings on the Church of St. Mary of the Angel can be read from the site's achievement space to its interior detail. On the other hand, the visual signs on the Indonesian Evangelical Church of Setrasari are not shown much, even its location on the second floor of Setrasari Mall with Giant Supermarket on the first floor is highly irrelevant. Starting from the space of achievement of the site to the form of interior detail does not explain much the relationship of space, form, and meaning. The absence of visual symbolic signs does not mean loss of meaning representation. The value of religiosity was born in cyberspace, presented more through audiovisuals such as the delivery of sermons, congregational praise, choirs, PowerPoint presentations, panel presentations, video clips, musical plays that are live shows rather than visual signs of physical form and space.